Value chain assessment tool for tourism sector companies: restaurants case - González Calle, María José (2025)
The social, economic, and cultural development of a country is closely linked to the performance of MSMEs, particularly in the gastronomic sector, due to their capacity to generate employment and stimulate tourism. This study aimed to design a value chain evaluation tool for restaurants, regarded as key actors in emerging economies. Amethodology combining the World Bank's approach and Porter's model was applied. The results led to the development of a tool structured in three stages: service production, marketing, and service provision, incorporating criteria adapted from primary and support activities. This flexible tool enables the diagnosis of business strengths andweaknesses, supporting decision-making, sectoral evaluation, and the formulation of productive development policies.